Archeology od ignorance in the conception of Nicolas of Cusa - Bańka, Józef (Folia Philosophica, 2003)
The author tries to prove that the general tendency in the development of the thought of Nicholas of Cusa is positive as it aims at extracting from human ignorance these pieces of positive knowledge that are the most valuable. The advantage of Nicholas of Cusa’s thought is that it refers not only to philosophy but also to the formal sciences (including mathematical ones). Therefore, his thought can be represented in the form of coherent sentences. Nicholas of Cusa’s frequent references to mathematics make it possible for us to discern in the philosopher’s thought some elements of the modern research methodology. According to the philosopher from Cusa, the task of mathematics is to use geometrical models and mathematical analogy, as they are the most efficient way of presenting experience in terms of a theoretical vision of the universe.